The Post Pandemic Education : A Blended Learning Approach For Teaching And Learning In Higher Education in New Normal Era - Muthahharah Thahir; Widiawati Widiawati; Nur Baitillah (International Journal of Ethno-Sciences and Education Research, 2023)
The Covid-19 virus that spreads very quickly causes everyone to have to practice social distancing and physical distancing to reduce its impact. The virus that has been endemic since the end of December 2019 has revolutionized the learning process held by every educational institution, including the learning process in universities. Previously, the learning process at universities was carried out face-to-face. When the covid-19 pandemic occurs, the learning process must of course continue to be carried out by minimizing the impact of covid-19 so that universities must be able to make changes quickly from face-to-face learning systems to online/online learning. Adopting online learning through the use of technology to continue to implement the Tri Dharma is one of the solutions chosen by each university so that the learning process can continue and the spread of the COVID-19 virus can be minimized. After covid-19 occurred and the new normal era began, the level of life gradually went on as before. Learning in higher education must of course be re-adjusted to existing conditions. Finally, blended learning is used as a solution to carry out the teaching and learning process in universities in the new normal era. Blended learning approach is believed to be one of the learning models that are considered more effective for learning in this new normal era. By continuing to use technology as a form of innovation in learning in the digitalization era, blended learning is also still carried out by continuing to prioritize the human touch side in its implementation where the face-to-face learning process with direct interaction certainly has its own advantages. Through the combination of the advantages of offline learning and online learning, blended learning appears as the best alternative in the higher education learning system so that learning is believed to be more meaningful and also supports independence in learning.